2014
DOI: 10.1016/j.cagd.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Rotation-minimizing osculating frames

Abstract: An orthonormal frame (f 1 , f 2 , f 3 ) is rotation-minimizing with respect to f i if its angular velocity ω satisfies ω · f i ≡ 0 -or, equivalently, the derivatives of f j and f k are both parallel to f i . The Frenet frame (t, p, b) along a space curve is rotation-minimizing with respect to the principal normal p, and in recent years adapted frames that are rotation-minimizing with respect to the tangent t have attracted much interest. This study is concerned with rotation-minimizing osculating frames (f , g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…RMFs are widely used in many applications in computer graphics, sweep surface modeling [19], generalized cylinder modeling [20,21] and motion design and control [22]. However, exact RMF (i.e., closed form) computation is non-trivial and thus a number of approximation techniques [5,[23][24][25] have been proposed. We employ RMFs as a reference coordinate system and represent the edited details in RMFs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…RMFs are widely used in many applications in computer graphics, sweep surface modeling [19], generalized cylinder modeling [20,21] and motion design and control [22]. However, exact RMF (i.e., closed form) computation is non-trivial and thus a number of approximation techniques [5,[23][24][25] have been proposed. We employ RMFs as a reference coordinate system and represent the edited details in RMFs.…”
Section: Related Workmentioning
confidence: 99%
“…We choose rotation minimizing frames (RMFs) [5,[23][24][25] for the requirement above. However, finding the explicit form of exact RMFs on general B-spline curves is known to be a non-trivial problem and thus many approximation techniques have been proposed in practice.…”
Section: Multilevel B-spline Curves With Orientation Of Detailsmentioning
confidence: 99%
“…As previously noted, the most commonly-studied RMF is the adapted frame, which is rotation-minimizing with respect to the tangent t. The Frenet frame is itself rotation-minimizing with respect to the principal normal p. A third possibility, a frame that is rotation-minimizing with respect to the binormal b, was studied in [20]. In the terminology of aerodynamics, these three frames define roll-free, pitch-free, and yaw-free motions.…”
Section: Other Rotation-minimizing Framesmentioning
confidence: 99%
“…It was shown in [20] that no DPH curves of degree less than 7 with rational osculating RMFs exist. The study of curves with such frames was extended in [42] to the rational case, based on the dual representation [30,41], and it was shown that rational curves with rational osculating RMFs of degree ≥ 6 exist, and the minimum degree of polynomial curves with this property is 7.…”
Section: Other Rotation-minimizing Framesmentioning
confidence: 99%
See 1 more Smart Citation